Synergistic anti-tumor activity of the mTOR inhibitor everolimus and gemcitabine for relapsed/refractory peripheral T cell lymphoma - Huang, Ling; Guo, Hanguo; Teng, Yan; Pang, Diwen; Zhang, Fen; Sun, Yichen; Ong, Choon Kiat; Tan, Jing; Li, Wenyu (Frontiers in Immunology, 2025)
BackgroundRelapsed/refractory (R/R) peripheral T-cell lymphoma (PTCL) patients face poor prognosis and limited therapies. The mTOR inhibitor everolimus and gemcitabine show modest efficacy as single agents in R/R PTCL, warranting investigation of combination regimens.MethodsThis study conducted a single-center retrospective analysis of 24 patients diagnosed with peripheral T-cell lymphoma, aged 18 to 70 years, who experienced relapse or refractory disease following at least one first-line chemotherapy regimen, and received treatment at Guangdong Provincial People’s Hospital between December 2017 and March 2021. CellTiter Glo and AnnexinV FITC/PI assays evaluated cell viability and apoptosis in vitro.ResultsThe combination showed significant efficacy: objective response rate (ORR) 70.8%, complete response (CR) rate 45.8%, median time to response 1.7 months. With median follow-up of 22.3 months (95% CI 5.7–39.0), median progression-free survival (PFS) was 9.9 months (95% CI 0–20.81), and median duration of response (DOR) 16.8 months. Patients with CR/partial response (PR) had longer PFS (18.7 vs. 1.2 months, P = 0.0007) and overall survival (OS) (30.9 vs. 5.8 months, P = 0.021) than those with stable/progressive disease. RNA-seq results showed that the combined therapeutic approach synergistically reduces cell viability and promotes apoptosis through the inhibition of the MYC signaling pathway.ConclusionEverolimus-gemcitabine combination exhibits synergistic antitumor activity, offering a potential therapeutic strategy for R/R PTCL.